La Question de L’adaptation du Texte Sacré aux Enfants: Le cas de L’histoire de la Fourmi et Salomon - نجم، أريج; عودة، أكرم عبدالرؤوف (الجامعة الأردنية - عمادة البحث العلمي, 2019)
شغلت ترجمة النصوص الدينية علماء الترجمة والمترجمين منذ قرون طويلة، لما لها من أهمية ثقافية وتربوية، ولما تطرحه من قضايا ترجمة معقدة. إذا لم يلق نقل هذه الترجمات إلى لغة الأطفال وتكييفها بما يتوافق وطبيعة الطفل وخصائصه التعليمية والتعلمية الاهتمام إلا حديثا. إذ يعيش الملايين من الأطفال المسلمين الذين لا يتقنون اللغة العربية في البلدان الناطقة بالفرنسية حيث لا يمكنهم دراسة دينهم، بسب علمانية معظم مدارس هذه الدول. وبالتالي تقوم الأسرة بتعليم القيم الدينية والثقافية لصغارها. تهدف هذه الدراسة إلى تكيف آيات من سورة النمل من الترجمة الفرنسية للقرآن، لتلائم الأطفال الفرنكوفونيين البالغة أعمارهم من 6-12 سنة. تبين هذه الدراسة نظريات التكيف وإشكالاته، والخروج باستراتيجيات تكيف مع القصة المبنية على علاقة الطفل بالحيوان، وعلاقة حشرة صغيرة ضعيفة مع مالك ونبي امتلك جبروت الإنس والجن.
Millions of Muslim children live in French-speaking countries. These children can barely speak the language of their countries of origin, particularly the Arabic language. With the absence of schools where Islam is taught, their only alternative is studying at secular schools like the French ones. Therefore, Muslim families pass on their cultural and religious values to young generations by exposing them to the translations of the works of their original cultures. The French translations of these works become one of the main channels that protect the ties between French-speaking Muslims and their origins. This hybridity evokes a sense of multiculturalism that enriches these people and the countries where they live: “A mind enclosed in one language and one culture does not think and end up repeating itself”.(Barthélémy, 2012, p.9).This study aims to adapt verses from Surah 27 An-Naml (The formis) from the French version of the translation of the Quran to French-speaking children aged between 6 to 12 years. The relationship between the child and the animal and the relationship between a king prophet (Solomon) and a tiny insect constitute a pedagogical ground for transmitting the moral values of Islam to children. After exploring the state of research literature, this paper will explore the main theories and strategies used in the process of adapting adult texts to the specific needs of children’s literature in order to apply them to the source text. It will also try to identify adaptation problems encountered during the translation process and suggest possible solutions.
Keywords: سيدنا سليمان عليه السلام -- القصة القرآنية -- قصة سليمان والنملة -- أدب الأطفال